2018
DOI: 10.1111/bcpt.13023
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Long‐Term Proton Pump Inhibitor Use: A Review

Abstract: Proton pump inhibitors (PPIs) are widely used, and concerns about overuse have been raised. Therefore, side effects are important to be aware of and several suggested side effects of long-term use have been studied. In this MiniReview, we sum up the evidence of side effects related to long-term PPI treatment. Suspected side effects are mainly related to increased susceptibility to infections, secondary hypergastrinaemia, impeded absorption of micronutrients or idiosyncratic reactions. Most of the potential sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
141
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(152 citation statements)
references
References 69 publications
1
141
0
10
Order By: Relevance
“…A similar practice of inappropriate prescription of acid suppressants is commonplace in veterinary medicine. Judicious use of acid suppressants is warranted, considering recent studies documenting adverse effects of long‐term PPI supplementation in people and animals …”
Section: Introductionmentioning
confidence: 99%
“…A similar practice of inappropriate prescription of acid suppressants is commonplace in veterinary medicine. Judicious use of acid suppressants is warranted, considering recent studies documenting adverse effects of long‐term PPI supplementation in people and animals …”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory effects of PPIs have also been observed in the renal collecting duct, in osteoclast resorptive pits and on lysosomal enzymes . The short‐term use of PPIs causes only mild side effects, whereas long‐term exposure has been associated with osteoporosis and bone fractures . In fact, since 2010, all manufacturers of PPIs in the USA are required by the Food and Drugs Agency (FDA) to label the drugs with a warning about possible hip, wrist and spine fractures when used in high doses or for an extended period of time (>1 year)…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The short-term use of PPIs causes only mild side effects, whereas long-term exposure has been associated with osteoporosis and bone fractures. [11][12][13][14][15][16] In fact, since 2010, all manufacturers of PPIs in the USA are required by the Food and Drugs Agency (FDA) to label the drugs with a warning about possible hip, wrist and spine fractures when used in high doses or for an extended period of time (>1 year). 17 Lysosomes are acidic organelles (pH 3.5) with membrane proton pumps.…”
mentioning
confidence: 99%
“…Because these drugs usually cause few adverse effects, they are usually available over‐the‐counter in many countries and there is an overall impression that their use is relatively not risky. In fact, possible adverse effects induced by PPIs include increased susceptibility to bacterial infections, deficient absorption of micronutrients, hypergastrinaemia and its consequences, dementia and kidney diseases . While these drugs are usually regarded as safe drugs, a number of studies have shown a variety of pleiotropic effects associated with the use of PPIs, which may be attributable to interactions of PPIs with other relevant biological mechanisms not directly associated with suppression of gastric acid secretion.…”
mentioning
confidence: 99%